Textual Parallel to the Vita of Constantine-Cyril the Philosopher: “Our God Is Like the Depths of the Sea” (Chapter 6) - Юрьевич Темчин, Сергей (Slavistica Vilnensis, 2002)
The author argues that the comparison of the Christian God to the depths of the sea, used by Constantine the Philosopher in his disputation with the Arabs (as described in chapter 6 of his Vita), goes back to the pseudo-Chrysostomian festal sermon for Holy Cross Day (14 September), and not to the homilies by Gregory of Nazianzus, as have been proposed by V. Vavřínek.